2018
DOI: 10.5194/bg-15-1-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on N<sub>2</sub> fixation and net nitrogen release of <i>Trichodesmium</i> in a field study

Abstract: Abstract. Dinitrogen fixation (NF) by marine cyanobacteria is an important pathway to replenish the oceanic bioavailable nitrogen inventory. Light is the key to modulating NF; however, field studies investigating the light response curve (NF-I curve) of NF rate and the effect of light on diazotrophderived nitrogen (DDN) net release are relatively sparse in the literature, hampering prediction using models. A dissolution method was applied using uncontaminated 15 N 2 gas to examine how the light changes may inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 67 publications
2
36
1
Order By: Relevance
“…By the end of August, the AWD shifted to a significant CO 2 source of about 0.7 mol C m −2 (Table 1). Accounting for the study period between January and August, this results in an ocean net annual CO 2 sink between 4 and 8 mmol m −2 d −1 , which are similar to the results by Yasunaka et al (2018). The winter-tosummer ocean CO 2 uptake estimates of 3.7 mol C m −2 (44 g C m −2 ) by Fransson et al (2001) in the Barents Sea in the upper 50 m, are nearly twice as large as our maximum estimate of 2.1 mol C m −2 (25 g C m −2 ).…”
Section: Monthsupporting
confidence: 86%
See 1 more Smart Citation
“…By the end of August, the AWD shifted to a significant CO 2 source of about 0.7 mol C m −2 (Table 1). Accounting for the study period between January and August, this results in an ocean net annual CO 2 sink between 4 and 8 mmol m −2 d −1 , which are similar to the results by Yasunaka et al (2018). The winter-tosummer ocean CO 2 uptake estimates of 3.7 mol C m −2 (44 g C m −2 ) by Fransson et al (2001) in the Barents Sea in the upper 50 m, are nearly twice as large as our maximum estimate of 2.1 mol C m −2 (25 g C m −2 ).…”
Section: Monthsupporting
confidence: 86%
“…The Oceanic Sink of Atmospheric CO 2 in Fram Strait Area and Its Variability Several studies estimating the air-sea CO 2 fluxes and the annual net CO 2 sink show that the Arctic Ocean, the Fram Strait and waters around Svalbard act as atmospheric CO 2 sinks (e.g., Tynan et al, 2016;Yasunaka et al, 2016Yasunaka et al, , 2018Fransson et al, 2017). The 18-year annual average of observed seawater f CO 2 and a self-organizing mapping technique showed that the Arctic Ocean acted as an ocean CO 2 sink between 8 and 12 mmol m −2 d −1 and a daily mean in a full annual cycle of 5 mmol m −2 d −1 (Yasunaka et al, 2018). In our estimates, the study area showed a small oceanic CO 2 sink until May at an average of 0.12 ± 0.06 mol C m −2 for the period January to May.…”
Section: Monthmentioning
confidence: 99%
“…The NFRs were measured using the dissolution method (Mohr et al ; Lu et al ) to avoid the problems of bubble dissolution. 15 N 2 gas (98.9%) from Cambridge Isotope Laboratories was used, and a blank was checked for contamination of bioavailable non‐N 2 15 N, as described in Dabundo et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The different vertical distribution of Trichodesmium and Richelia/Calothrix is attributable to different ecological niches for adapting light and nutrients (e.g., P, Si, and Fe). Laboratory and field culture experiments showed that Richelia/Calothrix (Foster et al, 2010;Villareal, 1990) seem more tolerant to low light than Trichodesmium (Breitbarth et al, 2008;LaRoche & Breitbarth, 2005;Lu et al, 2018) in deeper water column.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 97%